Problem-Based Learning to Improve Students’ Grammar Competence - Mukminatus Zuhriyah (IAIN Salatiga, 2017)
Grammar becomes one of the subjects studied in all Indonesian English Department. It is because grammar has the important role in all English skills. Grammar makes those four English skills meaningful. Somebody can be said as a master of English when he or she also masters grammar. Unfortunately, learning grammar is not as easy as what we think. It needs the effective method that can make the learners motivated and active in learning as well as in applying the grammar in the real life. Problem-based learning applied in this research is one of the alternatives that can help the learners learn grammar easily. This research was a collaborative action research whose general purpose to know whether or not Problem-based learning could improve the students’ grammar competence. Meanwhile, the specific purposes were to know the lecturer’s activities, the students’ activities, and the students’ responses when problem-based learning was implemented in grammar class. Nine students of the fifth semester of English department of education faculty of Hasyim Asy’ari University (UNHASY) Tebuireng Jombang in the academic year of 2016/2017 became the subjects of this research. The data got was from the observation notes and the grammar test. There was an improvement on students’ grammar competence from cycle one to cycle two. It was proven by their mean score from 66.7 in cycle one to 72.8 in cycle two. Meanwhile, the percentage of students passing the minimum mastery criteria was from 44.4 in cycle one and 88.9 in cycle two. So that it can be concluded that problem-based learning could improve students’ grammar competence.